The legacy of Leprosy - Ramji, Ashwath Narayan (Research and Humanities in Medical Education, 2019)
As scientists we look for intellectual advancement through every encounter, yearn for new knowledge, and search for ways to further our learning. We are programmed by our nurturing to identify, analyse, and solve. Horses with blinders, we are obtuse in our ignorance; however, our nature, if we allow it, will find emotional growth - some encounters will compel us to introspect, so the learning becomes about ourselves, even as we may struggle to align our (unrealistic and idealistic) views with the (subjectively bleak) reality.